Liver cancer burden attributable to high body mass index and high fasting plasma glucose in BRICS countries (1990–2021): a Global Burden of Disease 2021 analysis with projections to 2050 - Cai, Jianya; Lan, Yanhong; Wang, Ying; Cheng, Hongwei; Xu, Shuangta (Frontiers in Oncology, 2025)
BackgroundWith the escalating prevalence of obesity and diabetes, high body mass index (BMI) and high fasting plasma glucose (HFPG) have emerged as increasingly significant risk factors for liver cancer worldwide. This study evaluates the burden of liver cancer attributable to high BMI and HFPG in BRICS countries from 1990 to 2021 and projects future trends to 2050, drawing upon data from the Global Burden of Disease (GBD) Study 2021.MethodData on liver cancer burden, stratified by sex and age, were retrieved from the GBD database. Trends were assessed using estimated annual percentage change (EAPC) with 95% confidence intervals. Autoregressive integrated moving average (ARIMA) and exponential smoothing (ES) models were employed to generate future projections.ResultIn 2021, South Africa exhibited the highest liver cancer mortality rate attributable to high BMI, whereas India recorded the most rapid growth. Between 1990 to 2021, mortality and disability-adjusted life years (DALYs) associated with high BMI-related liver cancer increased substantially in China, particularly among older populations. The decomposition analysis revealed that epidemiological change was the dominant driver behind the rising burden in both China and India, with population growth being a secondary yet substantial factor. Epidemiological transitions accounted for the predominant rise in mortality and DALYs in China and India. Forecasts indicate persistent increases in liver cancer mortality and DALYs attributable to high BMI and HFPG through 2050.ConclusionThe liver cancer burden attributable to high BMI and HFPG is anticipated to escalate across BRICS countries. Enhanced efforts in prevention, early screening, and comprehensive management of obesity, diabetes, and metabolic disorders are indispensable to mitigate the projected impact.